Value chain analysis of potato in selected areas of Bogra and Munshigonj districts of Bangladesh - Hossain, Mohammad Anwar (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.